STUDI ANALISIS KONSEP TARBIYYAH MUHAMMAD RAWWAS SERTA REVELANSINYA TERHADAP PROBLEMATIKA KENAKALAN REMAJA - Mohammad Rindu Fajar Islamy; Usup Romli; Ganjar Eka Subakti; Saepul Anwar (Universitas Pendidikan Indonesia, 2021)
This study aims to analyze the concept of tarbiyyah of contemporary Muslim intellectual Muhammad Rawwas and its relevance to the dynamics of juvenile delinquency. Indeed, education was created in order to shape the personality of students who are religious and build their cognitive intellectuality so that they become a superior generation in the future. Increasing the penetration of global flows in the last few decades due to the current Covid-19 outbreak has resulted in the world of Indonesian education experiencing great challenges in order to stem the negative sides posed by students, especially regarding morality throughout Indonesia. This research study uses a mixed methods approach that combines quantitative and qualitative approaches. The number of respondents involved in the quantitative approach was 197 people, of which 149 were female, and the remaining 48 were male. This was taken through an interview with one of the principals to validate and strengthen assumptions in the field. The age range of students ranges from 15 to 18 years, all of which we take from the West Java region. The data collected was then analyzed using Miles and Huberman Theory. The results showed several findings including 1) The level of male delinquency is higher with a coefficient of 3.6 compared to female which is only 2.1, 2) The factors that influence juvenile delinquency are divided into two internal and external, 3) Application of the concept of tarbiyyah Muhammad Rawwas which includes nine principles which are extracted from the life journey of Rasulullah SAW can suppress cases of teenage acquaintances.Keyword: Al-Qur'an; Tarbiyah; Muhammad Rawwas; Juvenile Delinquency, Pandemic